2020
DOI: 10.3389/fmars.2019.00825
|View full text |Cite|
|
Sign up to set email alerts
|

Mesozooplankton and Micronekton Active Carbon Transport in Contrasting Eddies

Abstract: were sampled along the eastern coast of Australia. Depth stratified mesozooplankton and micronekton were collected using a Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS) and an International Young Gadoid Pelagic Trawl (IYGPT) equipped with an opening/closing codend. Sampling was undertaken at the center and edge of a frontal cold-core eddy (F-CCE Center and Edge) in 2015, and at the center of a cold-core eddy (B-CCE) and two warmcore eddies (R-WCE and WCE) in 2017. We assess the diel v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 106 publications
1
18
0
Order By: Relevance
“…Micronekton, organisms with a length in the range of 2-20 cm, have a stronger ability to migrate and wider migration range than zooplankton. Micronekton are one of the dominant components of mesopelagic biomes in the marine system (Catul et al, 2010;Kwong et al, 2020). Micronekton migrate to the surface (0-200 m) to feed at night and descend to the mesopelagic layers (200-1,000 m) to escape predators after sunrise, which is referred as diel vertical migration (DVM).…”
Section: Introductionmentioning
confidence: 99%
“…Micronekton, organisms with a length in the range of 2-20 cm, have a stronger ability to migrate and wider migration range than zooplankton. Micronekton are one of the dominant components of mesopelagic biomes in the marine system (Catul et al, 2010;Kwong et al, 2020). Micronekton migrate to the surface (0-200 m) to feed at night and descend to the mesopelagic layers (200-1,000 m) to escape predators after sunrise, which is referred as diel vertical migration (DVM).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, zooplankton alter their DVM in response to chemicals produced by fish, called kairomones ( 12 , 13 ), and to internal circadian rhythms that can cue migration during periods of polar midnight sun ( 14 ). DVM is not only important to understanding aquatic trophic dynamics, but it also impacts nutrient cycles worldwide, as organic matter consumed at the surface by migrators is transported to depth, metabolized, and released as dissolved inorganic carbon (respired), dissolved organic matter (excreted), and particulate organic matter (egested) ( 15 18 ).…”
mentioning
confidence: 99%
“…Kaartvedt et al ( 19 ) showed that mesopelagic fish swam upward beneath a passing storm, Frank and Widder ( 20 ) found that a transient influx of turbid water enhanced light attenuation and induced an upward migration of crustaceans and salps, and other studies show that cloudiness can influence vertical migration behavior on diel timescales ( 21 23 ). McLaren ( 24 ) proposed that during the day, zooplankton may be “resting” in deeper, cooler waters to save energy, and studies estimating migrator excretion and respiration rates at depth assume a constant rate of metabolic activity throughout daylight hours based largely on temperature and animal size ( 15 , 18 ). In situ observations of inactivity by animals at depth are for mesopelagic fishes that are large enough to be observed by submersibles ( 24 ), while less information is available for zooplankton.…”
mentioning
confidence: 99%
“…Retention of zooplankton within the subsurface eddy over PDC may also play a critical role in carbon cycling within the region. Mesoscale eddies have been hypothesized to be important carbon sinks, and that the role these features play in carbon cycling is highly dependent on the zooplankton communities they retain (Christiansen et al., 2018; Kwong et al., 2020). More work is necessary to determine if the subsurface eddy over PDC has any impact on the local carbon cycle and if it retains zooplankton communities that allow it to act as a carbon sink.…”
Section: Discussionmentioning
confidence: 99%